(untitled) (International Journal of Food and Nutritional Sciences, 2022)
AIM- The aim of the present investigation is to study the preliminary study of dried leaves of Cinnamomum Camphora. MATERIAL & METHODS- Dried leaves of Cinnamomum Camphora were procured from the medicinal garden and campus of Pharmacy College in the month of September, Bhopal, Madhya Pradesh, India. Around 500 gm dried leaves of Cinnamomum Camphora were coarsely powdered weighed and filled in Soxhlet apparatus for extraction. First the powdered drug was defatted with petroleum ether (60°C-80°C); Defatted drug was then dried and again filled in soxhlet apparatus for successively extraction with dichloromethane, ethyl acetate, methanol and water as solvent. The extraction was carried out for a period of 72 hrs. The extract obtained was dried in vacuum to remove excess solvent and were weighed for the determination of % yields. Qualitative chemical tests of all extracts were subjected to various chemical tests to detect various Phytoconstituents. The acute oral toxicity studies were carried out according to the guidelines set by the Organization for Economic Co- operation and Development (OECD), revised draft guideline 423. RESULTS- Dried leaves of Cinnamomum Camphora were extracted using pet ether, dichloromethane, ethyl acetate, methanol and water and the percentage yield was found to be 5.2, 7.8, 8.5, 9.7, 9.4 %. The preliminary phytochemical analysis revealed that different active constituent present in different extracts such as carbohydrates, proteins, amino acids, fat, oils, steroids, terpenoids, glycosides, alkaloids, tannins and other phenolics compounds. CONCLUSION- No toxic effects were observed at a higher dose of 2000 mg/kg body weight of Wistar rats. Hence, 1/ 10th dose was selected as effective dose or therapeutic dose. The cut off value of 200 and 1/5 dose double of 400 mg/kg were selected for further activity.